A Concept Paper of Balanced Scorecard for New Product Development - Zhengxiaoming, Aminaimu; Fernando, Yudi (KnE Social Sciences, 2019)
This study aims to review the concept of Balanced Scorecard (BSC) technique to develop a new product. BSC, as a strategic performance tool, has received closed attention from many organizations worldwide. However, the implementation has been limited. The globalization and economic upheaval have increased the challenges to the executive’s face and therefore need to find the right tools to overcome the challenges. The current paper focuses on the review of literature on the importance of BSC towards new product development and business performance. This paper suggests that the 4th generation balance scorecard leads the combination of the management system and performance measurement that brings up one big strategy maps, and possibly will use widely to satisfy the customer demands. This paper discusses the current issues and the emerging importance of BSC literature and suggests fruitful areas for further study.